The Relation of 25-Hydroxyvitamin D Level with Metabolic Syndrome in Type 2 Diabetes Mellitus Patients - Medityas Winda Krissinta; M.I. Diah Pramudianti; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Type 2 Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia. Metabolic Syndrome (MS) is a complex metabolic disorder like hyperglycemia, obesity, dyslipidemia, and hypertension. Vitamin D controls genes associated with the regulation of insulin and renin production. The aim of this study was to analyze the relation between total levels of 25-hydroxyvitamin D [25(OH)D] and the incidence of MS in type 2 DM patients. This was an observational study with a cross-sectional design conducted from October to November 2018 in Dr. Moewardi Hospital Surakarta on 84 people with type 2 DM. All subjects were 34-75 years old. The research data were analyzed with a 2x2 test table to determine the Prevalence Ratio (PR) of each study variable, then multivariate analysis with logistic regression was continued. The mean total level of 25(OH)D was 18.01±6.10 ng/dL. Bivariate and continued with multivariate PR analysis showed poor glycemic control with the incidence of MS (PR: 11.154; 95% Cl: 3.933-31.631; p=0.001); female sex (PR : 1.788; 95% Cl: 0.750-4.261; p=0.188); age < 50 year (PR: 1.644; 95% Cl: 0.614-4.404; p=0.321); and total 25(OH)D deficiency (PR: 1.250; 95% Cl: 0.317-2.022; p=0.637). Total 25(OH)D level was not associated with the incidence of MS in the type 2 DM patients. Further study was needed using healthy group control to explain the role of vitamin D in type 2 DM.